Comparative Evidence of an Exceptional Impact of Gene Duplication on the Developmental Evolution of Drosophila and the Higher Diptera - Bao, Riyue; Dia, Sammy E.; Issa, Hussein A.; Alhusein, Dalia; Friedrich, Markus (Frontiers in Ecology and Evolution, 2018)
The importance of gene duplication in developmental body plan evolution is well established, but for many megadiverse clades such as true flies (Diptera), a comprehensive understanding is still just emerging through comparative genomics. In a survey of 377 developmental gene families, we found that in addition to the pea aphid, which has been previously shown to be genome-wide enriched with gene duplicates and was included as positive control, more than twice as many expanded developmental gene families were observed in Drosophila (49) compared to mosquito (21), flour beetle (20), and honey bee (14). Synonymous sequence divergence estimates and ortholog conservation analyses in additional dipteran genomes revealed that most Drosophila gene duplicates are ancient and accumulated during a time window that reaches back to the origin of brachyceran flies, approximately 180 million years ago. Further, available genetic data suggest that more than half of the Drosophila developmental gene duplicates remained partially or even fully redundant despite their ancient separation. We therefore speculate that the exceptional accumulation of developmental gene duplicates in Drosophila and the higher Diptera was proximally driven by the evolution of fast development, benefiting from increased genetic robustness. At the same time, the concomitant increase of opportunities for gene duplicate diversification appears to have been a source for developmental and phenotypic innovation during the unparalleled diversification of brachyceran Diptera.